Angioid streaks in Jamaican patients with homozygous sickle cell disease. Issue 5 (May 1981) - Hamilton, A M; Pope, F M; Condon, P I; Slavin, G; Sowter, C; Ford, S; Hayes, R J; Serjeant, G R
Abstract : Angioid streaks were observed in 21 of 242 patients with homozygous sickle cell disease. Two morphological types were observed. There is no evidence that angioid streaks in Jamaican patients are related to pseudoxanthoma elasticum.